2009
DOI: 10.1016/j.spa.2009.07.005
|View full text |Cite
|
Sign up to set email alerts
|

On the dependence structure of wavelet coefficients for spherical random fields

Abstract: We consider the correlation structure of the random coefficients for a class of wavelet systems on the sphere (labelled Mexican needlets) which was recently introduced in the literature by [D. Geller, A. Mayeli, Nearly tight frames and space-frequency analysis on compact manifolds, Preprint, 2007. arxiv:0706.3642v2]. We provide necessary and sufficient conditions for these coefficients to be asymptotically uncorrelated in the real and in the frequency domain. Here, the asymptotic theory is developed in the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 32 publications
0
44
0
Order By: Relevance
“…(12) Now let N be the least integer larger than μ/2 + 1. The equality (12) implies l a N l Z l (cos θ) c l (2l + 1)l −2N+μ C .…”
Section: The Key Estimatementioning
confidence: 99%
“…(12) Now let N be the least integer larger than μ/2 + 1. The equality (12) implies l a N l Z l (cos θ) c l (2l + 1)l −2N+μ C .…”
Section: The Key Estimatementioning
confidence: 99%
“…Spherical needlets were recently introduced by [38,39], and further developed, and extended to general smooth compact Riemannian manifolds in [18][19][20]. In a random fields environment, needlets were investigated by [5,6], with a view to applications to the statistical analysis of CMB data; applications in the physical literature include [26,34,42], see also [12,15,16,30] and [31,35].…”
Section: Introductionmentioning
confidence: 99%
“…Remark 3 A generalization of this B-adic framework, in a different direction to the one of Guilloux et al (2009) can be found in Geller andMayeli (2009), Mayeli (2010), Lan and Marinucci (2009). The authors do not suppose that the function a (or b) is compactly supported and obtain localization and asymptotic uncorrelation results similar to Propositions 3 and 4.…”
Section: Assumption 1 There Exist M ≥ 3 and A M-differentiable Real Fmentioning
confidence: 98%